Информационная технология стратегического управления проектно-ориентированной организацией - Кадыкова, Ирина Николаевна; Ларина, Светлана Александровна; Чумаченко, Игорь Владимирович (НТУ "ХПИ", 2017)
Авторы раскрывают преимущества использования информационных технологий в управлении стратегией проектно-ориентированной организации в условиях турбулентного окружения. Предложенная авторами IT-технология стратегического управления ВУЗом как проектно-ориентированной организацией базируется на системе сбалансированной системы показателей и учитывает специфику функционирования организации. Возможность применения современных IT-технологий раскрывается на двух примерах: моделирование в системе Business Studio и реализация наиболее трудоемких элементов информационной технологии в среде MS Excel.

The authors reveal the advantages of the information technologies that are used in the management of project-oriented organization‘s strategy in a turbulent environment. IT-technology of university‘s strategic management, proposed by the authors, is based on the balanced scorecard method and takes into account the specifics of the organization‘s functioning. The university is considered as a project-oriented organization. The program algorithm for calculating compliance to the staff with respect to the index of scientific and professional activity of the teaching staff was developed. The possibility of using the modern IT-technology is displayed in two examples: modeling by Business Studio software and implementation of the most time-consuming elements of information technology in MS Excel software.
IT of project-oriented organization strategic management
Keywords: информационная технология; управление проектами; сбалансированная система показателей; стратегия; проектно-ориентированная организация; IT; project management; balanced scorecard; strategy; project-oriented organization